Sustainability and Corporate Social Responsibility in Digital Platform Companies - Khuan, Hendri; Bakri, Asri Ady; Lusianawati, Hayu (Westscience Press, 2023)
This research study conducts a comprehensive bibliometric analysis of the literature on sustainability and corporate social responsibility (CSR) within the context of digital platform companies. The analysis aims to uncover trends, gaps, and key contributors in this evolving intersection. By employing VOSviewer, a specialized bibliometric analysis tool, the study examines co-authorship networks, keyword co-occurrence, citation patterns, and publication trends. The findings shed light on the collaborative landscape, prevalent themes, influential works, and evolving research activity. The study's implications extend to academia, industry, and policy, guiding further research, informing business strategies, and fostering responsible practices in the digital economy.